2019
DOI: 10.1016/j.jvs.2018.04.064
|View full text |Cite
|
Sign up to set email alerts
|

Complex endovascular aneurysm repair is associated with higher perioperative mortality but not late mortality compared with infrarenal endovascular aneurysm repair among octogenarians

Abstract: Complex EVAR is associated with greater perioperative mortality compared with infrarenal EVAR among octogenarians. However, late outcomes, including the need for reintervention and all-cause mortality, are not significantly different. Larger aneurysms and chronic kidney disease portends greater risk of late death after EVAR, regardless of AAA complexity. These patient-related factors should be considered when offering endovascular treatment to older patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 21 publications
0
14
2
Order By: Relevance
“…By including all 82 consecutive patients that underwent complex EVAR, it was attempted to present an unselected “real-world” patient group, commensurate with patients seen in a daily clinical practice. The 30-day mortality rate found in the current study (7.3%) is higher compared with the mortality rate found by Van Calster et al 32 (4.9%) and lower compared with the 30-day mortality rates mentioned by Oderich et al 6 (8.2%) and Tran et al 7 (8.6%). The difference with Van Calster et al 32 could be explained by different procedures being included.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…By including all 82 consecutive patients that underwent complex EVAR, it was attempted to present an unselected “real-world” patient group, commensurate with patients seen in a daily clinical practice. The 30-day mortality rate found in the current study (7.3%) is higher compared with the mortality rate found by Van Calster et al 32 (4.9%) and lower compared with the 30-day mortality rates mentioned by Oderich et al 6 (8.2%) and Tran et al 7 (8.6%). The difference with Van Calster et al 32 could be explained by different procedures being included.…”
Section: Discussioncontrasting
confidence: 79%
“…Thirty-day mortality rates ranging from 3.4% up to 8.6% have been reported in complex EVAR, compared with an average of 1.2% in conventional EVAR. [6][7][8][9] Besides morbidity and mortality, patients undergoing complex EVAR are at risk of decline in functional performance. Living independently of care and maintaining quality of life are highly valued outcomes, especially in older patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Henstra et al analysed 272 pts of whom had a median age of 82 years and demonstrated that age itself is not a reason to withhold fenestrated endovascular aortic aneurysm repair (FEVAR) in the elderly, and choice of treatment should be based on the pt's comorbidities and preferences [126]. Yet, perioperative mortality is increased, whereas late mortality is not [127].…”
Section: Predicting Complications and Patient Selection: Anatomic Criteria Age Frailty Obesity And Familial Aortoiliac Aneurysm Or Dissecmentioning
confidence: 99%
“…Complex endovascular repair is reported to offer superior perioperative mortality rates when compared with conventional open repair of complex aneuryms 4 , 5 . The safety profile of F/B-EVAR has resulted in an increase in older patients being offered complex endovascular repair 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%